Factors to Strengthen the Ideological Immunity of Young People in the Process of Ideological Education - Аbdurazzakov Gulmurod Musurmonkulovich (Zien Journals, 2022)
This article discusses the need to be alert to the ideological processes in the hearts of young people in the process of globalization, not to allow an ideological gap, not to be influenced by the flow of dangerous information coming from various sources, and to strive to eliminate the evils of religious and other forms of fanaticism.
Keywords: глglobalization; ideology; dangerous information; modern thinking